The Effect of STEAM-Based Learning Assisted by Educational Games and Virtual Reality on Junior High School Students’ Learning Motivation in Basic Programming Materials - Riska Novianti; Achmad Buchori; Wijayanto (Cattleya Darmaya Fortuna, 2026)
This study is motivated by the need for technology-based learning innovations to enhance students’ learning motivation, particularly through the integration of the STEAM approach with educational games and virtual reality. This study aims to analyze the effect of STEAM-based learning assisted by educational games and virtual reality on students’ learning motivation. The method used was a quasi-experimental design with a pretest-posttest control group. The research subjects consisted of 56 students divided into an experimental class and a control class. Data were collected using a learning motivation questionnaire that had been tested for validity and reliability, while data analysis was conducted using multiple linear regression tests with IBM SPSS Statistics 27. The results showed that simultaneously, educational games and virtual reality had a significant effect (sig. 0.031 < 0.05) on students’ learning motivation. However, partially, educational games did not have a significant effect (sig. 0.091 > 0.05), and virtual reality also did not show a significant effect (sig. 0.984 > 0.05). The coefficient of determination (R²) value of 0.242 indicates that both variables contributed 24.2% to students’ learning motivation. These findings suggest that the integration of technology in STEAM learning has the potential to improve learning motivation; however, the effectiveness of each medium still needs to be optimized to produce a more significant partial effect.